2019
DOI: 10.1063/1.5110578
|View full text |Cite
|
Sign up to set email alerts
|

Sonic horizon dynamics for quantum systems with cubic-quintic-septic nonlinearity

Abstract: We study the sonic horizon formation problem for quantum system incorporating septic nonlinearity, which is modeled by the nonlinear Schrödinger equation (NLSE) with nonlinearity up to septic order. Based on the F-expansion method combined with modulus-phase transformation, we derived the soliton solutions of such NLSE for the one-dimensional and three-dimensional scenarios, from which the sonic horizon formation dynamical variables are derived. We identify that the distribution of system flow velocity and sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Wang et al have shown in their work that the distribution of speed of system flow and the speed of sound determining the occurrence of the sonic horizon is in agreement with the corresponding quantities obtained from a pure numerical evaluation for quantum system incorporating septic nonlinearity modeled by NLS equation [32]. An essential manifestation of the intensity dependence of the refractive index in nonlinear optical media rises through self-phase modulation (SPM) [33], which leads to spectral spreading of optical pulses.…”
Section: Introductionsupporting
confidence: 53%
“…Wang et al have shown in their work that the distribution of speed of system flow and the speed of sound determining the occurrence of the sonic horizon is in agreement with the corresponding quantities obtained from a pure numerical evaluation for quantum system incorporating septic nonlinearity modeled by NLS equation [32]. An essential manifestation of the intensity dependence of the refractive index in nonlinear optical media rises through self-phase modulation (SPM) [33], which leads to spectral spreading of optical pulses.…”
Section: Introductionsupporting
confidence: 53%
“…Recently, some models have been derived by reckoning without the term chromatic dispersion and adding higher-order nonlinear terms from the literature. Some of the models developed in this context are: NLSE having arbitrary refractive index [25][26][27][28], NLSE including anti-cubic nonlinearity [29], NLSE having Kudryashovʼs sextic power-law of nonlinear refractive index [9,[30][31][32][33][34], cubic-quintic NLSE [35][36][37], NLSE with cubic-quintic-septic nonlinearities [38,39], NLSE with cubic-quintic-septic-nonic (CQSN) nonlinearities [5,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%